Hormone‐mediated modulation of the electromotor CPG in pulse‐type weakly electric fish. Commonalities and differences across species. Issue 1 (28th January 2020) - Borde, Michel; Quintana, Laura; Comas, Virginia; Silva, Ana
Abstract: Like stomatogastric activity in crustaceans, vocalization in teleosts and frogs, and locomotion in mammals, the electric organ discharge (EOD) of weakly electric fish is a rhythmic and stereotyped electromotor pattern. The EOD, which functions in both perception and communication, is controlled by a two‐layered central pattern generator (CPG), the electromotor CPG, which modifies its basal output in response to environmental and social challenges. Despite major anatomo‐functional commonalities in the electromotor CPG across electric fish species, we show that Gymnotus omarorum and Brachyhypopomus gauderio have evolved divergent neural processes to transiently modify the CPG outputs through descending fast neurotransmitter inputs to generate communication signals. We also present two examples of electric behavioral displays in which it is possible to separately analyze the effects of neuropeptides (mid‐term modulation) and gonadal steroid hormones (long‐term modulation) upon the CPG. First, the nonbreeding territorial aggression of G. omarorum has been an advantageous model to analyze the status‐dependent modulation of the excitability of CPG neuronal components by vasotocin. Second, the seasonal and sexually dimorphic courtship signals of B. gauderio have been useful to understand the effects of sex steroids on the responses to glutamatergic inputs in the CPG. Overall, the electromotor CPG functions in a regime that safeguards the EOD waveform. However, prepacemaker influences and hormonal modulation enable an enormous versatility and allows the EOD to adapt its functional state in a species‐, sex‐, and social context‐specific manners.